Penerapan Asas Konsensualisme dalam E-Payment QRIS sebagai Bukti Elektronik dalam Hukum Acara Perdata (Pusat Riset dan Inovasi Nasional, 2026)
The development of financial technology has driven significant transformations in the non-cash payment system in Indonesia, one of which is through the use of the Quick Response Code Indonesian Standard (QRIS). The use of QRIS in civil transactions relates not only to the technical aspects of payments but also has legal implications in the civil realm, particularly regarding the application of the principle of consensualism and the status of electronic evidence in the Indonesian civil procedural law system. This study aims to analyze the application of the principle of consensualism in QRIS e-payment transactions as electronic evidence in civil procedural law. The research method used is normative legal research with a statutory and conceptual approach. The results indicate that QRIS transactions meet the principle of consensualism due to the agreement of the parties, and QRIS can be qualified as a valid electronic document as long as it meets the requirements for electronic system reliability and information integrity as stipulated in laws and regulations. However, the evidentiary power of QRIS is not perfect and requires the support of other evidence, with the final assessment resting with the judge based on the principle of independent evidence in civil procedural law.